2019
DOI: 10.1186/s13019-019-0956-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of valve noise on the quality of life of patients after mechanical mitral valve replacement in a Chinese population

Abstract: Objective To investigate the effect of valve noise on the quality of life (QOL) in Chinese patients who underwent mechanical mitral valve replacement. Methods We enrolled a total of 103 patients who underwent mechanical mitral valve replacement (MVR, CM valve in 52 patients, SJM valve in 51 patients) from January 2016 to December 2016 in our institution and used the SF-36 as an instrument to assess patients’ QOL. Results Patients’ QOL improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 14 publications
(20 reference statements)
0
15
0
1
Order By: Relevance
“…9) Although a number of studies have focused on the effect of artificial valve sound on QoL, few studies have investigated the effect of artificial heart valve sounds on patients' QoL at different time points. [4][5][6][7] Moritz evaluated the sound pressure levels of the CarboMedics (CM) valve, Bjork Shiley (BS) valve, and Duromedicus-Edwards (DE) valve at 1 cm of the chest wall and found that the sound pressure levels of the BS and DE valves were significantly higher. 10) Similarly, Laurens et al evaluated the sound pressure levels of CM, BS, and SJM valves at 1 cm from the chest wall and found that the sound pressure levels of BS valves (55.4 dB) were significantly higher than those of the CM valves (46.0 dB) and SJM valves (44.1 dB).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9) Although a number of studies have focused on the effect of artificial valve sound on QoL, few studies have investigated the effect of artificial heart valve sounds on patients' QoL at different time points. [4][5][6][7] Moritz evaluated the sound pressure levels of the CarboMedics (CM) valve, Bjork Shiley (BS) valve, and Duromedicus-Edwards (DE) valve at 1 cm of the chest wall and found that the sound pressure levels of the BS and DE valves were significantly higher. 10) Similarly, Laurens et al evaluated the sound pressure levels of CM, BS, and SJM valves at 1 cm from the chest wall and found that the sound pressure levels of BS valves (55.4 dB) were significantly higher than those of the CM valves (46.0 dB) and SJM valves (44.1 dB).…”
Section: Discussionmentioning
confidence: 99%
“… 9 ) Although a number of studies have focused on the effect of artificial valve sound on QoL, few studies have investigated the effect of artificial heart valve sounds on patients’ QoL at different time points. 4 7 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly more researchers are concerned that the noise generated by mechanical valves may negatively affect the quality of life of patients. Studies have shown that at least one-third of patients after mechanical heart valve replacement are concerned about the sound from the mechanical valves and believe that the sounds will affect their quality of life, although few complain that the sounds seriously affect survival [14][15][16]. A case report even described a patient who underwent secondary surgery for bioprosthetic valve replacement due to noise intolerance to mechanical valve closure [17].…”
Section: Discussionmentioning
confidence: 99%
“…There was full of literature that addressed the intersection of quality of life and noise pollution worldwide. A number of measurement tools were adopted to reflect the relationship between noise and HRQOL, such as WHOQOL-BREF [32], Nijmegen Cochlear Implant Questionnaire [33], SF-36 [34], and Hearing Environments and Reflection on Quality of Life questionnaire [35]. A cross-sectional questionnaire-based study shows that individuals with high noise sensitivity (NS) tend to have degraded HRQOL compared to individuals with low NS [36].…”
Section: Introductionmentioning
confidence: 99%